Metabolic Syndrome Induces Over Expression of the Human AT1R: A Haplotype-Dependent Effect With Implications on Cardio-Renal Function. (5th October 2017) - Jain, Sudhir; Puri, Nitin; Rana, Anita; Sirianni, Natalie; Mopidevi, Brahmaraju; Kumar, Ashok
Abstract: BACKGROUND: The transcriptional regulation of the human angiotensin receptor subtype 1 (AT1R) gene in pathophysiologies, like the metabolic syndrome, is poorly understood. The human AT1R gene has polymorphisms in its promoter that can be arranged in 2 haplotypes. Variants -810T, -713T, -214A, and -153A always occur together (Hap-I) and variants -810A, -713G, -214C, and -153G form Hap-II. We have hypothesized that high fat diet will alter cellular transcriptional milieu and increase hAT1R gene expression in a haplotype-dependent manner. This will set up an AT1R-mediated feed-forward loop promoting inflammation, oxidative stress, and hypertension in Hap-I mice. METHOD: Since Hap-I of the human AT1R gene is associated with hypertension in Caucasians, we generated transgenic (TG) mice with Hap-I and Hap-II and studied the physiological significance of high fat diet (HFD) on haplotype specific gene expression. Animals were fed with HFD for 20 weeks followed by blood pressure (BP) analysis and collection of their tissues for molecular and biochemical studies. RESULTS: After HFD treatment, as compared to Hap-II, TG mice with Hap-I show increased expression of hAT1R gene and higher BP; suppression of antioxidant defenses (HO1, SOD1) and increased expression of IL-6, TNFα, IL-1β, NOX1. In vivo ChIP assay has shown that transcription factors CEBPβ, STAT3, and USF bind more strongly to the chromatin obtained from Hap-I TG mice. CONCLUSIONS: Taken together, our results suggest, that after HFD treatment, as compared to Hap-II, the TG mice with Hap-I overexpress the AT1R gene due to the stronger transcriptional activity, thus resulting in an increase in their BP.